Kanunisasi Hukum Islam di Indonesia - Ajub Ishak (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
This paper explores the implementation of Islamic law in Indonesia. Islamic law has been established and legally recognized in Indonesian Muslim society which certainly has the power to force the application of Islamic law to the people, especially Muslims. Canons of Islamic law derived from revelation to man; therefore, it is different with the canons of Islamic jurisprudence that there is no compulsion for the implementation involves aspects of human life, especially Muslims. In Indonesia, the canons of Islamic law had been implemented but are still limited in the scope of civil Islam. More specifically related to family law and its implementation is particularly devoted to the Muslim community.